Economic development, external shocks, and food security in Tajikistan - Akramov, Kamiljon T.; Shreedhar, Ganga (International Food Policy Research Institute, 2012)
The combination of the recent global food and financial crises has had severe negative consequences on food security in Tajikistan. High dependence on food imports has made Tajikistan extremely vulnerable to the increasing global food prices and the volatility and transmission of global food prices was an important dimension of the food price crisis in the country. Excessive reliance on labor remittances exacerbated Tajikistan’s food insecurity and the vulnerability of its households. This study examines the impact of recent food and economic crises on macro- and household-level food security in the country using macro-, sectoral-, and household-level data from national and international sources. The study also discusses overall trends in economic growth and poverty reduction, constraints and bottlenecks on agricultural growth and productivity, and other policies that may mitigate the negative effects of future external shocks.